Effect of bonding temperature on microstructure and shear strength of the dissimilar Al/Al-27Si joints bonded by partial transient liquid phase bonding. (May 2019) - Xu, Lei; Wang, Haibo; Sun, Qingzhu; Wan, Weicai; Chen, Hongsheng
Graphical abstract: Highlights: Soldering seam with many eutectic phases is obtained in the Al/Al-27Si joints. Morphologies of Si transform from granular particles into needle-like shape at 560 °C. Penetration of eutectic phases into the Al matrix along grain boundaries is generated. Non-planar bonding interfaces are developed and become more non-planar with temperature. Shear strengths of joints firstly increase and then decrease with bonding temperature. Abstract: The microstructure and shear strength of the Al alloy/Al-27Si alloy (Al/Al-27Si) joints with Cu interlayer bonded at different temperatures were investigated in the present study. Results show that a soldering seam with many eutectic phases is obtained in the Al/Al-27Si joints. These eutectic phases are mainly composed of θ -CuAl2 phase, α -Al phase and Si phase. With the increase of bonding temperature, the width of soldering seam and the average size of Si particles gradually increase, while the density of eutectic θ -CuAl2 phase deceases. The morphologies of Si phases transform from the granular particles into the needle-like shape when the temperature increases to 560 °C. The penetration of eutectic phases into the Al matrix along the grain boundaries is generated and the non-planar Al/soldering-seam interfaces are developed. With the increase of bonding temperature, the shear strengths of Al/Al-27Si joints firstly increase because of the better joining effect and less micro-cracks, and then decrease resulting from the morphology transformation of Si phases. The maximum shear strength of 70.4 MPa is achieved at 550 °C.